Effects of different long-term exercise interventions on working memory in children and adolescents: a network meta-analysis - Guo, Xuejun; Wang, Junyu; Liang, Jie; Xie, Ting; Zhang, Lin (Frontiers in Psychology, 2025)
ObjectivesTo compare the relative efficacy of different exercise modalities on working memory accuracy and reaction time in healthy children and adolescents.MethodsA systematic review and network meta-analysis was conducted in accordance with PRISMA guidelines (CRD420251005303). PubMed, Medline, Embase, the Cochrane Central Register of Controlled Trials, and Web of Science were searched from inception to March 1, 2025. Randomized controlled trials examining the impact of any exercise intervention (e.g., aerobic exercise, dance, high-intensity interval training, sports games, mixed exercise) versus control on working memory accuracy and/or reaction time were eligible. Standardized mean differences (SMDs) with 95% confidence intervals (CIs) were calculated, and a random-effects model was applied to account for between-study heterogeneity. The surface under the cumulative ranking curve (SUCRA) was used to determine the relative ranking of each modality.ResultsThirty-three studies met inclusion criteria for working memory accuracy, and eight studies contributed data on reaction time. Dance demonstrated the highest SUCRA ranking for accuracy (87.8%), and was significantly superior to control (SMD = 0.67, 95% CI 0.13 to 1.21). Aerobic exercise ranked first for reaction time (93.6%), outperforming control (SMD = −0.40, 95% CI −0.69 to −0.11 for accuracy; SMD = −0.82, 95% CI −1.26 to −0.38 for reaction time compared with mixed exercise). Mixed exercise consistently showed lower rankings for both outcomes.ConclusionDistinct exercise modalities differentially affect working memory components in young populations. Dance and aerobic exercise appear most beneficial—dance maximizes accuracy, while aerobic exercise optimizes reaction time. Tailoring exercise interventions to specific cognitive targets may enhance working memory development and inform practical, evidence-based strategies in educational and clinical settings.Systematic review registrationRD420251005303.